Contemporary management - Jones, Gareth R. (McGraw-Hill Irwin, 2009)
Improve student learning outcomes using Connect, our easy-to-use homework and learning management solution that embeds learning science and award-winning adaptive tools to improve student results. Incorporate recent developments in management theory and research with current examples of how managers of companies large and small have responded to changes taking place in business. Infuse real managers who brought about change within their organization using their Manager as a Person feature allowing students to see real-life on-the-job challenges